International tourism in the sustainable development goals framework - Pochernina, Natalia; Почерніна, Наталя Вікторівна; Почернина, Наталья Викторовна; Popova, Tetiana; Попова, Тетяна Вікторівна; Попова, Татьяна Викторовна; Vasylchenko, Olena; Васильченко, Олена Олегівна; Васильченко, Елена Олеговна (School of Economics and Management in Public Administration in Bratislava, 2021)
The purpose of the paper was to reveal the cumulative characteristics of international tourism for the implementation of the Sustainable Development Goals. The tourism competitiveness indices of Ukraine were analysed in comparison with the EU countries, and the directions on increasing the efficiency of international tourism in Ukraine in the framework of the Sustainable Development Goals were substantiated. According to the Travel & Tourism Competitiveness Index for the period 2007-2019, Ukraine was found to be on lower positions than the EU countries, although in a few components of the index it had a competitive advantage compared with some countries of the European Union. To achieve the Sustainable Development Goals and the principles of the Global Code of Ethics for Tourism, Ukraine should concentrate on such dimensions as the increase of the economic and social value of T&T sector, the transition to a new mode of T&T management using Destination Management Organizations, and the implementation of the tourism impact assessment. In this context, the highest priority is given to the rural, mountain, ecological, cognitive-cultural and educational international kinds of tourism.
Keywords: international tourism; Sustainable Development Goals; tourism competitiveness indices; efficiency of international tourism